2007
DOI: 10.1021/jp066070v
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman Scattering of ZnO Quantum Dots on Silver Colloids

Abstract: Enhancement of the Raman signals of ZnO quantum dots on Ag colloids was studied. Unique ZnO/Ag nanostructure materials were obtained by self-assembly of Ag nanocrystals using ZnO nanoparticles as seeds. The morphology and optical properties of ZnO/Ag core/shell particles are dependent on the quality of deposited Ag. The surface plasmon absorption band of Ag shifts toward lower energy due to the interaction between Ag and ZnO quantum dots. The intensities and orders of multiphonon fingerprint Raman lines of ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 21 publications
8
82
0
Order By: Relevance
“…These deficient electrons on the Ag surface consequently induce the broadening and red shifting of the surface plasmon band, consistent with previous reports that electron deficiency in metal nanoparticles shifts the surface plasmon band to a longer wavelength [32,33]. Shan et al reported the absorption features of ZnO quantum dot/Ag nanocomposites [34]. They found that the ultraviolet absorption of ZnO/Ag nanocomposites had no change and the visible absorption broadened, weakened and red-shifted, which implied that the ZnO quantum dots almost had no change in size and the interaction between ZnO quantum dots and Ag was weak.…”
Section: Methodssupporting
confidence: 87%
“…These deficient electrons on the Ag surface consequently induce the broadening and red shifting of the surface plasmon band, consistent with previous reports that electron deficiency in metal nanoparticles shifts the surface plasmon band to a longer wavelength [32,33]. Shan et al reported the absorption features of ZnO quantum dot/Ag nanocomposites [34]. They found that the ultraviolet absorption of ZnO/Ag nanocomposites had no change and the visible absorption broadened, weakened and red-shifted, which implied that the ZnO quantum dots almost had no change in size and the interaction between ZnO quantum dots and Ag was weak.…”
Section: Methodssupporting
confidence: 87%
“…Also, multiphonon Raman scattering is enhanced by the strongly localized electromagnetic field of the metal plasmon, as observed in other types of composite systems. [106,107] These modified properties again reflect the mutual influence of interfacial electron communication that is achieved upon formation of a inorganic heterojunction.…”
Section: (A) Direct Epitaxial Heterogeneous Nucleationmentioning
confidence: 83%
“…In comparison with Ag/SiO 2 (385 nm) and Ag/NaY (390 nm) catalysts, the main characteristic surface plasma resonance (SPR) peaks of Ag 0 nanoparticles for Ag/Al 2 O 3 and Ag/TiO 2 samples show a large redshift to 450 nm and 500 nm, respectively. It has been known that the electron in Ag 0 surface can spill out of the classical radius and can be transferred into affinity levels of the support [28][29][30][31][32]. The spill-out of the electrons will lead to a decreased electron density and consequently the redshift of the Mie resonance frequency according to equation [29]:…”
Section: Diffuse Reflectance Uv-vis Spectramentioning
confidence: 99%